2019
DOI: 10.2147/dmso.s183811
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cardioprotective effects of a ruthenium (II) Schiff base complex in diet-induced prediabetic rats</p>

Abstract: Background Prediabetes and the onset of cardiovascular diseases (CVD) are strongly related. Prolonged hyperglycemia has been identified as a major contributing factor in the pathogenesis of CVD and diabetic complications. The management of hyperglycemia and prediabetes-associated vascular complications rely on pharmacotherapy and lifestyle intervention strategies. However, patients still take the conventional drugs and neglect lifestyle intervention; therefore, newer alternative drugs are required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…However, studies indicate that complications often associated with T2DM begin during pre-diabetes [ 7 ]. Previous studies done in our laboratory have found that micro- and macrovascular changes leading to complications such as cardiovascular complications and non-alcoholic fatty liver disease seen in T2DM have been shown to begin during a prediabetic state [ 37 , 38 ]. Hence, this current study was aimed at investigating the changes in the functioning of the HPA axis in a HFHC diet-induced prediabetic rat model.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies indicate that complications often associated with T2DM begin during pre-diabetes [ 7 ]. Previous studies done in our laboratory have found that micro- and macrovascular changes leading to complications such as cardiovascular complications and non-alcoholic fatty liver disease seen in T2DM have been shown to begin during a prediabetic state [ 37 , 38 ]. Hence, this current study was aimed at investigating the changes in the functioning of the HPA axis in a HFHC diet-induced prediabetic rat model.…”
Section: Discussionmentioning
confidence: 99%
“…All chemicals and drugs were of analytical grade and purchased from standard commercial suppliers. Previous studies showed that the dose of the ruthenium complex used in this study was nontoxic 23 , 24 …”
Section: Methodsmentioning
confidence: 81%
“…We speculate that these findings may be due to the metal complex activating several key reactions, in particular those catalyzed by heme oxygenase 1, biliverdin reductase, and UDP-glucuronosyltransferase enzymes, which play an important role in bilirubin homeostasis 47 , 49 . Although we have not investigated these reactions in this study, this metal compound has been shown to have cardioprotective properties in diet-induced prediabetes rats and we speculate that these effects could be, in part, attributed to its effects on the synthesis of bilirubin in the liver 24 . Recent studies have identified bilirubin to be a major contributor to the total antioxidant capacity in blood 47 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, studies indicate that complications often associated with T2DM begin during prediabetes (7). Previous studies done in our laboratory have found that micro-and macrovascular changes leading to complications such as cardiovascular complications and non-fatty liver disease seen in T2DM have been shown to begin during a prediabetic state (36,37). Hence, this current study was aimed at investigating the changes in the functioning of the HPA axis in a HFHC diet-induced prediabetic rat model.…”
Section: Discussionmentioning
confidence: 95%